Student Perceptions On The Lifestyle Of Kip Scholarship Students - Fitri Yanti; Vethy Octaviani; Bayu Risdiyanto (Penerbit Jurnal Indonesia, 2024)
This research was conducted with the aim of students’ perceptions on lifestyle of KIP scholarship recipients. This research uses descriptive qualitative methods. In this study using data collection techniques through observation, interviews, and documentation. The technique of taking research informants uses random purposive sampling. The results of the study show that the perceptions of students on lifestyle of KIP scholarship recipients are quite good, it can be seen from internal factors such as background, experience, personality, value system, and self-acceptance work together to shape students’ perceptions of lifestyle of KIP scholarship recipients so as to encourage that KIP scholarship recipients must have a simple and responsible lifestyle. External factors which can be seen such as intensity, experience, personality, value system, and self-acceptance. External factors such as intensity, size, contrast, movement, repetition, familiarity, and novelty work together to form complex and diverse perceptions among students, emphasizing the importance of simplicity and responsibility in the use of KIP scholarships.